Application of Plastic Waste (Polyethylene and Synthetic Polymers) as a Soil Modifier in Subgrades and Shallow Foundations - Eshkiknezhad, Morteza H. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
Polyethylene terephthalate (PET) is one of if not the most commonly consumed type of plastic in industry and they can be readily spotted as they are used for water, pop bottles, and a few types of packaging. Although alternative recycling solutions can help in the conservation of landfills, they are not a definite solution. In this study, as an alternative solution to the waste problem of PET products, been used to find an alternative solution to further enhance sand properties to make them suitable for construction zones. Despite other studies in this direction, none of them have reached the substantial results that this study has achieved. The reason being is the presence of a novel methodology that creates a remarkable interlocking strength between aggregates using plastics. This method which includes heating both sand and plastic particles up to the melting point of plastics has better effects on unconfined compression and shear strength of sand than plastic strips combined with sand in a solid form. The plastic waste percent used in this study were 2.5, 5, 7.5, and 10 percent of the dry weight of sand in 4 different sample preparation groups (SPM-1, SPM-2, SPM-3, and SPM-4). The results indicated up to 3745kPa compressive strength and 8.6 times improvement in shear strength of sand for SPM-3 in a melted plastic form.

ÖZ: Polietilen tereftalat (PET), endüstride en yaygın tüketilen plastik türlerinden biri değilse de, su, pop şişeler ve birkaç ambalaj türü için kullanıldıkları için kolayca fark edilebilirler. Alternatif geri dönüşüm çözümleri, düzenli depolama alanlarının korunmasına yardımcı olsa da kesin bir çözüm değildir. Bu çalışmada, PET ürünlerin atık sorununa alternatif bir çözüm olarak, kum özelliklerini daha da geliştirmek ve inşaat alanlarına uygun hale getirmek için alternatif bir çözüm bulmak için kullanılmıştır. Bu konuda önceki çalışmalar PET’i katı olarak fiber şeklinde kum ile karıştırmak surety ile gerçekleştirilmişti. Bu çalışmada, PET kum tanecikleri arasında dikkate değer bir kenetlenme gücü sağlayan yeni bir yöntem denenmiştir. Hem kumun hem de plastik parçacıkların plastiklerin erime noktasına kadar ısıtılmasını içeren bu yöntem, katı halde kumla karıştırılmış plastik fiberlere göre kumun serbest sıkıştırma ve kesme mukavemeti üzerinde çok daha iyi etkiler elde edilmesine yardım etmiştir. Kullanılan plastik atık yüzdeleri, 4 farklı numune hazırlama grubunda (SPM-1, SPM2, SPM-3 ve SPM-4) kuru kum ağırlığının yüzde 2,5, 5, 7,5 ve yüzde 10'u kadardır. Sonuçlar, erimiş plastik formda SPM-3 numune grubu için yaklaşık 3745 kPa'ya kadar basınç dayanımı ve kumun kesme dayanımında yaklaşık 8.6 kat iyileşme olduğunu gösterdi.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2022. Supervisor: Assoc. Prof. Dr. Eriş Uygar.
Keywords: Thesis Tez; Civil Engineering Department; Aggregates (Building materials)--Concrete; Aggregates (Materials)--Civil Engineering; Construction Engineering--Supplementary Cementitious Materials--Waste Electronic Plastics; Soil; Sand; Waste; Plastic bottle; Polyethylene terephthalate (PET); Shear strength; Compressive strength